Combining Ability and Gene Effects for Harvest Index in Durum Wheat - Singh, R K; Sangwan, R S; Choudhary, R K (Annals of Arid Zone, 2016)
Parents with good general combiner were A 9-30-1 for biomass and grain yield, Raj-1555 for biomass and harvest index and DWL 5023 for grain yield and harvest index. Hybrids DWL 5023 x Meghdoot was good combination for biomass, grain yield and harvest index. Dominance component of variation was important for all traits Â·under study. The traits barring harvest index were inherited by more number of dominant alleles than recessive with symmetrical in distribution. The tall growing A 9-30-1 was observed with maximum dominant genes while dwarf DWL 5023 had maximum recessive genes for these traits.